Improvement of Saccharomyces propagation performance through oxygen-enriched air and aeration parameter variation - Beugholt, Alexander; Geier, Dominik Ulrich; Becker, Thomas (Frontiers in Chemical Engineering, 2023)
A variety of yeast applications in the food and beverage industry require individual and reproducible yeast propagation at high yields and consistent quality. One quality-determining parameter for yeast propagation is effective aeration to avoid oxygen depletion. Therefore, this work investigated three important aeration parameters: airflow, pulse time, and oxygen concentration, for their influence on yeast propagation. The aeration of a propagator involves phase transitions which are gradient-driven processes and can be accelerated with higher gradients between the liquid medium and the gas bubbles. In this study, oxygen-enriched air generated with membrane filters was used to aerate the system in an easy and cost-efficient way without the need for expensive technical gas usage. Propagation experiments were carried out in a pilot-scale reactor equipped with a membrane filter system for enhanced oxygen concentrations in ingas and online sensors for representative monitoring of the process. The membrane filter system is based on the separation of nitrogen in compressed air, leading to oxygen enrichment. Using oxygen-enriched air for propagation aeration showed higher oxygen transfer into the medium and the anaerobic process time caused by oxygen depletion due to high cell numbers was reduced by an average of 7.4% for pulsed aeration. Additionally, we conducted experiments with controlled measures of dissolved oxygen using different oxygen concentrations for aeration. The main objective of this study is to present a new and affordable optimization of propagation aeration using membrane filtration to enrich process air. The results showed increased cell counts for higher ingas oxygen concentrations and no negative impact on cell vitality was observed. Hence, our investigations showed that using oxygen-enriched air reduced the frequency of pulsed aeration, thus hindering foam formation, a limiting factor of the yeast propagation process.